LITERATURE CIRCLES AS COLLABORATIVE LEARNING TECHNIQ UES IN SENIOR HIGHSCHOOL - Karima Putri Rahmadina, - (2018)
The demand of teaching reading strategy that fits to equip students to cope with both academic needs and other functional competence requirements increases over time. Literature Circles proposed by Harvey Daniels (1994) has been highly praised for its qualification in assisting students to have a more meaningful reading experience. This research aims to qualitatively review the way Literature Circles function as Collaborative Learning Techniques on Senior High school students in Indonesia. The study was concluded within four consecutive meetings in one of Senior High Schools in Bandung with the data collected through participant observation, interview and document analysis. The findings of the study revealed that Literature Circles allows a learning environment that (1) supported the learner to have a meaningful and supportive interactions with their peers; (2) displayed responsibility of oneself and to others; (3) were reflective of its own practices, all of which support a Collaborative Learning environment in EFL classroom. Furthermore, it was also revealed that Literature Circles aided Learner Autonomy and Zone of Proximal Development (ZPD) to develop;---Tuntutanterhadapstrategipembelajaranmembaca yang cocokuntukmenyokongpesertadidikmengatasikebutuhanakademikjugakebutuhankompetensifungsionallainnyaterusmeningkatseiringberjalannyawaktu. Literature Circles, dipeloporioleh Harvey Daniels (1994) telahbanyakdipujiataskapabilitasnyadalammembantupesertadidikuntukmendapatkanpengalamanmembaca yang bermakna. Penelitianinibertujuanuntukmengulascara Literature Circles berfungsisebagaiteknikpembelajarankolaboratif di sekolahmenengahatas di Indonesia secarakualitatif. Studiiniselesaidalamempatpertemuanberturut-turut di salahsatusekolahmenengahatas di Kota Bandung dengan data didapatdariobservasipesertadidik, wawancaradananalisisdokumen. Berdasarkanhasilpenelitian, Literature Circles ditemukandapatmenyediakansuasanapembelajaran yang: (1) membantupesertadidikberinteraksidengansuportifdanbermakna; (2) menampilkantanggungjawabterhadapdirisendiridan orang lain; (3) reflektifterhadappraktekkerjakelompok, yang mana mendukungterjadinyasuasanapembelarankolaboratif di kelasEFL (English as Foreign Language). Selainitu, Literature Circles jugadapatmembantuberkembangnyaotonomisiswadanZPD (Zone of Proximal Development).